Designing, producing and exemplifying videos to support reflection and metacognition for in-service teachers training - Valentina Toci; Loredana Camizzi; Serena Goracci; Rachele Borgi; Francesca De Santis; Laura Coscia; Francesco Perrone; Maria Elisabetta Cigognini; Maria Chiara Pettenati (Je-LKS: Journal of E-Learning and Knowledge Society, 2015)
In this paper we document a six-phase video production process designed to support teachers’ continuous professional development in three disciplinary areas: scientific, linguistic-literary and foreign languages areas. This production has been carried out within the NOP1 - National Operational Programme funded by European structural funds and conducted by INDIRE between 2007 and 2014.The originality of this work lies in the co-research action performed by the team involved (researchers, teachers, instructional designers, video director, etc.) aimed at capturing meaningful professional practices enacted by teachers in their classes for the achievement of a given educational goal. The documented and exemplified production process can, not only function as a guide for the production of educational videos, but is also strongly characterized by its reflective and meta-reflective functions for Teacher Professional Development or TPD. Several examples of videos are described and referenced in the paper.